GENDERED DIMENSIONS OF CLIMATE CHANGE IN GILGIT-BALTISTAN: A FEMINIST POLITICAL ECOLOGY APPROACH (Contemporary Journal of Social Science Review, 2025)
This study explores the gendered dimensions of climate change in Gilgit-Baltistan, Pakistan, through the lens of Feminist Political Ecology (FPE). Drawing on qualitative data from semi-structured interviews, focus group discussions, and participant observations across three ecologically vulnerable districts Hunza, Ghizer, and Nagar the research examines how women experience, perceive, and adapt to climate-induced challenges such as glacial melt, erratic rainfall, and resource scarcity. The findings reveal that while women bear a disproportionate burden of environmental stress due to gendered labor expectations, restricted mobility, and limited institutional access they also act as critical agents of local adaptation through traditional ecological knowledge, community-based practices, and informal resilience strategies. However, these contributions are routinely overlooked in formal climate policy and planning. The study highlights the emotional and care burdens that climate change imposes on women and critiques the gender-blind nature of state and NGO interventions. It concludes that addressing climate vulnerability in Gilgit-Baltistan requires not only technical solutions but also structural transformation recognizing women’s agency, redistributing decision-making power, and embedding intersectional, decolonial, and gender-transformative frameworks into regional climate governance.